FACEBOOKING TOWARD DEATH: HOW DIGITAL LEGACY IMPACTS CURATION IN ONLINE SETTINGS - Pattwell, Ashley B. (AoIR Selected Papers of Internet Research, 2015)
This paper asks whether increased attention to notions of online legacy or digital afterlife could impact social media and other online behavior. Put another way, if networked technologies are imagined as an opportunity for not just identity performance, but identity preservation, would online activity show signs of curation?